THE IMPACT OF THE GOLD MINING ON THE SOCIAL, ECONOMIC, ANDCULTURAL IN THE BOMBANA DISTRICT SOUTHEAST SULAWESI PROVINCE - Usman Rianse; Weka Gusmiarty Abdullah; Abdi La Abdi; Ilma Sarimustaqiyma Rianse; Zulfikar La Zulfikar; Wa Kuasa Baka; La Ode Midi; Weka Widayati (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
The phenomenon of a gold mine brings a lot of changes in people's daily life in the Bombana District. This study aims to: (a) Aware of the social and cultural changes in society before and after the gold mining business, and (b) Knowing the changes in people's income before and after the gold mining business. The study population is the people who are in the gold mining sites. This study result, namely: (a) Gold mining have negative impact on social, economic, and cultural of communities around the gold mining area. Social, economic, and cultural societies tend to be in better shape before the gold mining. Average income communities after the gold mining increase by Rp 755.392 per month. (c) Gold mining do not increase the welfare of society, especially for farmers. The implication of this study is the government should strictly supervise and tighten even a moratorium against IUP, and gold mining companies should have corporate social responsibility (CSR) in the form of incentives to the affected communities of the businesses under their management in the fields of education, health, agriculture, economics, and culture as well as other aspects relating to the welfare of society.